Evaluasi Pengembangan Dan Pola Pembinaan Federasi Olahraga Rekreasi Masyarakat Indonesia Dalam Olahraga Rekreasi di Jawa Tengah - Ruman Ruman; Raditya Pratama; Efdal Prastiyo (Badan Penerbit STIEPARI Press, 2022)
The research aims to determine the development and pattern of sports coaching of the Indonesian Community Recreational Sports Federation (FORMI) in recreational sports in Central Java. The research method uses descriptive qualitative using an ex post fact approach. This research aims to examine events that have occurred and then trace them back to find out the factors that could have caused these events. The subjects of this research are the human resources in the management of FORMI Central Java, namely the chairman, secretary, treasurer and division heads. The data collection technique uses data triangulation with interview guidelines, observation and documentation. The research was carried out based on interview guidelines that had been prepared and approved by expert validators. Data analysis in this research was done by data reduction, data presentation and verification. Based on the interview guide, the results of the interview data show that the development of recreational sports coaching patterns at FORMI Central Java has fulfilled the provisions for running an organization in the form of a coaching and development process, but the level, good or bad, of the uptake of community ideas that can be realized depends on the management and supportive government. Based on data found through interviews and documents obtained, of all the activities carried out for the development and development of recreational sports in Central Java, only 43% were realized.